The process of biosorption of heavy metals in bioreactors loaded with sanitary sewage sludge - Barros,A. J. Morais (2006)
This work on the process of biosorption of nickel and chromium in an ascendant continuous-flow, fixed packed-bed bioreactor of sanitary sewage sludge was conducted in a search for solutions to the environmental problem caused by heavy metals. Analysis of the results demonstrated that the absorbent had an extraordinary capacity for biosorption of the heavy metals studied at about 9.0 pH of the effluent, with a removal percentage of over 90.0% for the two metals. Chemometric study results demonstrated that 20 days of the experimental system function were sufficient for achieving the maximum efficiency of sorption of the heavy metals studied by the sanitary sewage sludge employed.